Evolution and outcomes of sentinel lymph node mapping in vulvar cancer. Issue 3 (March 2020) - Broach, Vance; Abu-Rustum, Nadeem R; Sonoda, Yukio; Brown, Carol L; Jewell, Elizabeth; Gardner, Ginger; Chi, Dennis S; Zivanovic, Oliver; Leitao Jr, Mario M
Abstract : Objectives: To characterize our institutional experience with sentinel lymph node (SLN) biopsy in patients with vulvar cancer. We describe the oncologic outcomes of these patients and the utilization of SLN detection techniques over time. Methods: A retrospective analysis of all patients who underwent inguinofemoral SLN biopsy as part of their treatment for vulvar cancer at Memorial Sloan Kettering Cancer Center from January 1, 2000 to April 1, 2019. Patients were included in this analysis if they underwent inguinofemoral SLN biopsy for vulvar cancer, irrespective of presenting factors such as histology, tumor size or laterality. An "at-risk groin" was defined as either the right or left groin for which SLN biopsy of inguinofemoral lymph nodes was performed. Results: A total of 160 patients were included in our analysis, representing 265 at-risk groins. 114 patients had squamous cell histology representing 195 at-risk groins. Of the 169 negative groins in patients with squamous cell carcinoma, the 2 year isolated groin recurrence rate was 1.2%. SLN detection rate, irrespective of modality, was 96.2%. Technetium-99 (TC-99) + blue dye detected SLNs in 91.8% of groins; TC-99 + indocyanine green detected SLNs in 100% of groins (p = 0.157). Among the 110 groins that underwent mapping with TC-99 and blue dye, 4 patients had failed mapping with blue dye and mapped with TC-99 alone (3.6%). Among the 96 groins that underwent mapping with TC-99 and ICG, 14 patients failed to map with TC-99 and mapped with indocyanine green alone (14.6%). Conclusions: SLN mapping in vulvar cancer is reliable and oncologically effective. The utilization of indocyanine green for mapping has increased over the past decade and is associated with high rates of SLN detection.